Objective evaluation of fat tissue induration after breast reconstruction using a deep inferior epigastric perforator (DIEP) flap. Issue 3 (4th May 2019) - Sowa, Yoshihiro; Yokota, Isao; Fujikawa, Kei; Morita, Daiki; Taguchi, Tetsuya; Numajiri, Toshiaki
Abstract: Problems in breast reconstruction with deep inferior epigastric perforator (DIEP) flaps include postoperative fat induration and necrosis. A resulting clinical symptom is palpable indurated tissue, but it is difficult to measure the stiffness of transplanted fat tissues objectively at a deep site. The ability to perform shear-wave elastography (SWE) was recently added to some common ultrasonic echo devices, enabling objective three-dimensional measurements of tissue stiffness. In this study, we measured the stiffness of transplanted DIEP flaps using SWE to examine the effects of measurement sites, flap size and perforator patterns on stiffness. The subjects were 26 patients who showed induration of a transplanted flap on palpation in follow-up observation performed more than 6 months after breast reconstruction with a DIEP flap. The effects of the weight of the transplanted flap, and the diameter, number and location of the perforators on the stiffness of fat tissue were also analyzed. Within each zone, distal regions showed higher values, but in Zone II, significantly higher stiffness was also found in the proximal region. Multivariate regression analysis including all measurement sites, the weight of transplanted flap, and diameter, number and location of perforators showed that the stiffness of fat tissue was significantly higher in subjects with a larger weight flap. For safe reconstruction, it will be useful to examine the stiffness of fat tissue in individual regions of a transplanted flap retrospectively, because the examination results can be used in actual clinical practice.